1987
DOI: 10.1177/014107688708000208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carotid Compression, as Assessed by near Infrared Spectroscopy, upon Cerebral Blood Volume and Haemoglobin Oxygen Saturation

Abstract: Near infrared spectroscopy, a recently developed optoelectronic technique, has been studied as a possible method of monitoring the adequacy of cerebral perfusion in 22 patients who were candidates for carotid endarterectomy. Using this technique, changes in haemoglobin volume, haemoglobin oxygen saturation and redox level of cytochrome-c-oxidase were recorded from the frontoparietal region during routine carotid compression tests performed under continuous electroencephalographic (EEG) monitoring. A highly sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…To (Ferrari et al, 1986(Ferrari et al, , 1987(Ferrari et al, , 1992. This agrees with the known fact that under normal conditions in healthy subjects the ratio of the [tHb] to rCBV (the hematocrit) does not change significantly during short periods of time such as the duration of typical functional activation experiments.…”
Section: Introductionsupporting
confidence: 88%
“…To (Ferrari et al, 1986(Ferrari et al, , 1987(Ferrari et al, , 1992. This agrees with the known fact that under normal conditions in healthy subjects the ratio of the [tHb] to rCBV (the hematocrit) does not change significantly during short periods of time such as the duration of typical functional activation experiments.…”
Section: Introductionsupporting
confidence: 88%
“…Several groups of investigators have used NIR spectroscopy to observe changes in in tracerebral haemoglobin and cytochrome aa3 oxygenation on an arbitrary scale in ex perimental animals [11] and human subjects [1,6,7]. In studies of newborn infants, we have recently shown that quantitative mea surements of the chromophores are feasible (by application of the Beer-Lambert law) and that a number of additional haemody namic indices including cerebral blood flow and blood volume may be derived [5,13], NIR spectroscopy thus offers the prospect of monitoring cerebral oxygenation and hae modynamics in sick infants.…”
Section: Introductionmentioning
confidence: 99%
“…1 Applications include monitors of fetal physiology, 2-4 during cardiac surgery, 5,6 muscle function, 7-10 and neonatal, 11 pediatric, 12 and adult brain. [13][14][15][16][17][18][19] A number of NIRS instruments are now available that detect changes in optical attenuation from several wavelengths of light, and although a variety of algorithms have been applied to attempt quantification, accuracy of these instruments remains a concern.The NIRO 300 (Hamamatsu Photonics) provides a continuous online measurement of tissue oxygen index (TOI) using spatially resolved spectroscopy. 20,21 We have previously determined that TOI reflects cerebral oxygenation to a high degree of sensitivity and specificity during carotid surgery, 20 an indication that NIRS can show clinically relevant estimations of cerebral hemodynamic and oxygen changes in the adult head (Figure 1).…”
mentioning
confidence: 99%
“…In adults, normal TOI values have been reported to range from 65% to 85%. 14,36 -41 Although a number of authors have compared NIRS with other techniques such as jugular bulb oxygen saturation (SjO 2 ), transcranial Doppler ultrasonography and somatosensory-evoked potential 15,37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] or with neurologic events, few have attempted to define an absolute threshold for ischemia. 13,14,16,17,46,[57][58][59] Most studies of this type using NIRS make no attempt to correct for extracranial contributions to signal changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation